Instilling Core Islamic Values In Industrial Relations In Malaysia - Norman Zakiyy Chow Jen-T'Chiang (FACULTY OF LAW UNIVERSITAS JENDERAL SOEDIRMAN, 2024)
Vol. 21 Issue 1, January 2021 E-ISSN 2407-6562 P-ISSN 1410-0797 JDH Vol. 21 (No. 1): page 149-158 | DOI: 10.20884/1.jdh.2021.21.1.2868